Bystander activation and autoimmunity (2019)
The interaction over time of genetic, epigenetic and environmental factors (i.e., autoimmune ecology) increases or decreases the liability an individual would have to develop an autoimmune disease (AD) depending on the misbalance between risk and protective effects. Pathogens have been the most common antecedent events studied, but multiple other environmental factors including xenobiotic chemicals, drugs, vaccines, and nutritional factors have been implicated into the development of ADs. Three main mechanisms have been offered to explain the development of autoimmunity: molecular mimicry, epitope spreading, and bystander activation. The latter is characterized by auto-reactive B and T cells that undergo activation in an antigen-independent manner, influencing the development and course of autoimmunity. Activation occurs due to a combination of an inflammatory milieu, co-signaling ligands, and interactions with neighboring cells. In this review, we will discuss the studies performed seeking to define the role of bystander activation in systemic and organ-specific ADs. In all cases, we are cognizant of individual differences between hosts and the variable latency time for clinical expression of disease, all of which have made our understanding of the etiology of loss of immune tolerance difficult and enigmatic. © 2019 Elsevier Ltd